Intense blue and green photoluminescence emissions at room temperature in barium zirconate powders - Cavalcante, L. S.; Sczancoski, J. C.; Espinosa, J. W. M. [UNESP]; Mastelaro, V. R.; Michalowicz, A.; Pizani, P. S.; Vicente, Fábio Simões de [UNESP]; Li, M. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
Intense blue and green photoluminescence (PL) emissions were observed at room temperature in barium zirconate (BaZrO(3)) powders prepared by chemical method. The powders were analyzed by X-ray diffraction (XRD), X-ray absorption near edge spectroscopy (XANES), extended X-ray absorption spectroscopy (EXAFS) and ultraviolet-visible (UV-vis) absorption spectroscopy. The XRD patterns indicated the presence of a secondary phase of BaCO(3) in BaZrO(3) powders heat treated at 773K. K-edge XANES data revealed that Zr atoms presents in at least two Zr environments. EXAFS investigations showed strong bond length dispersion in the first coordination shell around Zr atoms. EXAFS analysis indicated that Zr atoms are coordinated by 6 oxygen in BaZrO(3) powders heat treated at 973 K. UV-vis measurements suggested the presence of intermediary energy levels into the band gap of BaZrO(3) powders heat treated at 773K. The intense PL emission in BaZrO(3) powders can be attributed to the two Zr environments or ZrO(5)-ZrO(6) clusters. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Disordered systems; Clusters; Chemical synthesis; Order-disorder effects; EXAFS